NSCAs Performance Training Journal - Nutrition (NSCAs Performance Training Journal, 2010)
Rikki Keen:The Importance of Vitamin D in Human Performance This featured article presents recent research on the effect and value of vitamin D, offers information on the symptoms of vitamin D defi ciency and provides suggestions to help improve athletic performance.